Golf turf management - McCarty, Lambert B. (Lambert Blanchard), 1958-; Taylor and Francis (Boca Raton, FL : CRC Press, an imprint of Taylor and Francis, 2018)
Golf Turf Management provides information on major agronomic and economic topics related to building and maintaining a viable golf course. The book features basic and applied information on available grasses including selection and use; applied turfgrass physiology; soils and soil amendments; environmental concerns; and comprehensive information on turfgrass physiology, plant nutrition, turf fertilizers, and water management. It discusses managing turf diseases, insects, and weeds; turf cultural practices; managing greens and tees as well as corporate course management strategies.Color photographs throughout illustrate concepts and topics including all major pest problems associated with golf courses and various agronomic practices necessary for successful and profitable course operation. The book suggests strategies to develop best management practices for golf courses including personnel and financial considerations when developing and implementing annual budgets, leasing versus buying equipment, and managing inventory. This book features sixteen chapters organized in a logical sequence conducive for teaching and practical use. Drawing on the author's more than thirty years of experience and research, the author brings together a wealth of information on how to optimize golf turf management and performance. Golf Turf Management is the only complete, up-to-date text dedicated to agronomic practices and personnel management practices necessary for fiscal success.
Turfgrasses. Turfgrass Physiology and Environmental Stresses. Soil Chemical and Biological Properties. Soil Physical Properties and Drainage Characteristics. Golf Course Construction and Renovation. Turfgrass Establishment and Grow-In. Plant Nutrition and Turf Fertilizers. Water Management. Turf Cultural Practices. Managing Greens and Tees. Integrated Pest Management. Turfgrass Diseases and Nematodes. Turfgrass Insects. Turfgrass Weeds and PGR Use. Pesticide Use and Calibration. Budgets and Personnel Management.
Keywords: Golf courses -- Maintenance; Turf management; Turfgrasses; Pests -- Control; Production management; TECHNOLOGY & ENGINEERING / Environmental / General; TECHNOLOGY & ENGINEERING / Environmental / Water Supply